Clinical assessment of gepotidacin (GSK2140944) as a victim and perpetrator of drug–drug interactions via CYP3A metabolism and transporters. Issue 4 (23rd January 2023) - Barth, Aline; Perry, Caroline R.; Shabbir, Shaila; Zamek‐Gliszczynski, Maciej J.; Thomas, Sebin; Dumont, Etienne F.; Brimhall, Darin B.; Nguyen, Dung; Srinivasan, Meenakshi; Swift, Brandon
Abstract: Gepotidacin is a novel triazaacenaphthylene antibiotic in phase III development. Based on nonclinical in vitro characterization of gepotidacin metabolism, two phase I studies were conducted in healthy participants to investigate clinical drug–drug interactions (DDIs). We assessed gepotidacin as a DDI victim with a potent cytochrome P450 (CYP) 3A4/P‐glycoprotein (P‐gp) inhibitor (itraconazole), potent CYP3A4 inducer (rifampicin), and nonspecific organic cation transporter (OCT)/multidrug and toxic extrusion transporter (MATE) renal transport inhibitor (cimetidine) via single doses of gepotidacin before and after co‐administration with multiple doses of the modulator drugs. Gepotidacin DDI perpetrator potential for P‐gp inhibition (digoxin) and CYP3A4 inhibition (midazolam) was evaluated via single doses of the two‐drug cocktail without and with gepotidacin. The DDI magnitudes were interpreted based on area under the concentration‐time curve (AUC). A weak DDI (AUC increase 48%–50%) was observed for gepotidacin co‐administered with itraconazole. A clinically significant decrease in gepotidacin plasma AUC (52%) was observed with rifampicin coadministration, indicating a moderate DDI. There was no DDI for gepotidacin with cimetidine; a unique biomarker approach showed increased serum creatinine (24%), decreased renal clearance of creatinine (21%), and N1‐methylnicotinamide (39%), which confirmed extensive MATE inhibition and partial OCT2 inhibition. Gepotidacin was not a P‐gp DDI perpetrator, although the maximum plasma concentration of digoxin increased (53%) and is potentially clinically relevant given its narrow therapeutic index. Gepotidacin demonstrated weak CYP3A4 inhibition with midazolam (<2‐fold AUC increase). There were no new safety‐risk profile findings. These results will inform the safe and efficacious clinical use of gepotidacin when co‐administered with other drugs.